Research on the influence of team psychological capital on team members’ work performance - Jiao, Yongji; Zhang, Xiaoman; Lu, Siwen; Wu, Zimo; Deng, Yuqian (Frontiers in Psychology, 2022)
Abstract: Team psychological capital is the positive psychological state of a team and has a positive impact on the human resource management and performance management of the team. Team members’ work performance, as a component of team performance, has an important impact on improving team performance. However, there is less cross-level impact analysis between the two. The purpose of this paper is to explore the mechanisms of the cross-level effects of team psychological capital on members' performance. A paired questionnaire survey was administered to 387 human resource management team members from 86 human resource management teams across China, and SPSS 22.0, AMOS 23.0, and HLM 6.08 software were used to analyze the questionnaire data at the same level and across levels. The test shows that the cross-level positive effect of team psychological capital on team members' work performance is established, and the cross-level mediating role of team members' psychological capital and team support between the two is established. It enriches the cross-level research from team to individual, refines and enriches the research on the impact of team psychological capital on individual behavior, and provides new ideas for team management in companies. Therefore, when conducting team management, enterprises can enhance team members’ psychological capital by improving team psychological capital, thereby improving team members’ work performance and team efficiency.